Strategi Storytelling untuk Meningkatkan Moral Peserta Didik - Trisnawati, Tri Endang; Fadillah, Nurul; Azwa, Nurul; Yulastri, Resti (Jurnal Budi Pekerti Agama Islam, 2025)
The advancement of digital technology encourages the need for innovative learning strategies capable of strengthening students’ moral character amid the decline in discipline, responsibility, and empathy among learners. This study aims to analyze how project-based digital storytelling influences the improvement of students’ morals and how its implementation process occurs within an educational context. The research method used is library research by examining books, journals, and relevant scientific sources related to students’ moral development, project-based learning, and digital storytelling. The analysis was conducted through content analysis to identify key concepts, findings from previous studies, and the relationship between storytelling strategies and the internalization of moral values. The results indicate that digital storytelling is effective as a learning medium because it can integrate cognitive, affective, and technological aspects into a meaningful learning experience. Through the processes of planning, scriptwriting, digital production, and project presentation, students are actively involved in understanding and internalizing moral values such as honesty, empathy, responsibility, and discipline. In addition, digital narratives can build emotional connectedness that strengthens moral feeling and encourages students’ moral action in daily life. These findings imply that project-based digital storytelling can serve as an innovative pedagogical strategy to reinforce character education in schools, especially in facing the challenges posed by technological development and behavioral changes in the digital generation.